Two new species of Lepanthes (Pleurothallidinae, Orchidaceae) from the Alto de Ventanas, Colombia - Vieira-Uribe, Sebastián; Moreno, Juan Sebastián; Espinosa, Felipe (Phytotaxa, 2022)
Two new species of Lepanthes, L. pembertonii and L. hwangiae, from the North of the Central Cordillera of the Colombian Andes are described and illustrated. Both were found while conducting research in Alto de Ventanas natural reserves with the objective of improving knowledge of the orchid flora of the department of Antioquia, Colombia. Comparison with their morphologically relatives and taxonomical and ecological notes are given.